PENGUATAN PONDASI BANGUNAN EKONOMI ISLAM - Harahap, Ikhwanuddin (Institut Agama Islam Negeri Padangsidimpuan, 2015)
Conventional economic system was uneguel on spritualization dimension of human life. The impacts of it are the high competition between people, exploitation on earth, exploitation on human being, etc.Â Islamic economic concern on both of human need, biological need and spritual need. It because Islamic Economi has good and strong foundation.